PEMODELAN INDEKS PEMBANGUNAN MANUSIA MENGGUNAKAN SPATIAL PANEL FIXED EFFECT (Studi Kasus: Indeks Pembangunan Manusia Propinsi Jawa Tengah 2008 - 2013) - Novian Trianggara; Rita Rahmawati; Hasbi Yasin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
The success of a country could be seen from the condition of it society. A country needs to have developed society, a way to establish it is by human development. Human development is formed by three basic components, they are long and healthy life, knowledge, and decent living. Some indicators that represent these three components are summarized in one single value, the Human Development Index. This study models the Human Development Index for each city in Central Java using econometric approach by considering the specific spatial effect. The independent variable used were health facilities representing health component, School Participation Rate that represents education component, and Poverty Percentage that represents component of decent living standard. By using Spatial Panel Fixed Effect the best model is Spatial Autoregressive Model (SAR) with the influencing independent variabels are school participation rate and poverty percentage, with R2 of 99.54%.Keyword: HDI, Spatial, Panel, Fixed Effect